2020
DOI: 10.1016/j.cmet.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Metabolism Shapes T Helper Cell Responses through Regulation of Epigenetic Reprogramming

Abstract: Epigenetic modifications on DNA and histones regulate gene expression by modulating chromatin accessibility to transcription machinery. Here we identify methionine as a key nutrient affecting epigenetic reprogramming in CD4 + T helper (Th) cells. Using metabolomics, we showed that methionine is rapidly taken up by activated T cells and serves as the major substrate for biosynthesis of the universal methyl donor S-adenosyl-L-methionine (SAM). Methionine was required to maintain intracellular SAM pools in T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
193
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(209 citation statements)
references
References 62 publications
13
193
2
1
Order By: Relevance
“…Indeed, metabolomics studies performed by Bian and colleagues confirmed dramatically decreased intracellular methionine and SAM levels upon methionine starvation 3 . This is in line with recent studies, which described a rapid turnover and a reduction of up to 98% of the SAM pool within hours of starving cells of methionine 8,9 . Being the methyl donor for various methyltransferases, SAM concentrations directly affect the levels of H3K79me2, an active gene mark in mammalian cells.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, metabolomics studies performed by Bian and colleagues confirmed dramatically decreased intracellular methionine and SAM levels upon methionine starvation 3 . This is in line with recent studies, which described a rapid turnover and a reduction of up to 98% of the SAM pool within hours of starving cells of methionine 8,9 . Being the methyl donor for various methyltransferases, SAM concentrations directly affect the levels of H3K79me2, an active gene mark in mammalian cells.…”
Section: Figuresupporting
confidence: 91%
“…In mammals, methionine is essential for de novo protein synthesis and required for the production of S‐adenosylmethionine (SAM), a universal methyl donor required for DNA and RNA methylation and substrate for multiple histone and protein methyltransferases. Thereby, SAM links nutrient availability and cellular metabolism directly with epigenetic regulation 8,9 . Indeed, metabolomics studies performed by Bian and colleagues confirmed dramatically decreased intracellular methionine and SAM levels upon methionine starvation 3 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The model predicted different underlying mechanisms causing the nutrient-responsive carbon overflow compared with the growth rate-dependent carbon overflow ( Figure 4B, S1B, S4B). It suggested that nitrogen limitation besides activating pathways related to nitrogen metabolism also activated the tetrahydrofolate (THF) cycle (C1 metabolism) affecting folate and methionine biosynthesis together with the precursor metabolite pathways (serine, chorismate) which important as these changes are reported to influence mitochondrial dynamics and play an important role in cancer metabolism ( Figure 4B, S1B, S4A) (Gao et al, 2018;Roy et al, 2020). The activation of these pathways led to not just C2 overflow (ethanol) but also C1 overflow (formate) under nitrogen limitation which we validated by measuring formate in culture samples ( Figure 4B, S1B, S4A).…”
Section: Energy Metabolism Trade-off Controls Proteome Abundance and mentioning
confidence: 99%
“…High-protein diets were particularly suggested to modulate in ammatory concentrations in patients with obesity and diabetes (15), and in the ageing population (16,17). On the other hand, a low-protein diet especially low-methionine diet was shown to bene cially in uence glucose intolerance (18) and modulate immune-in ammatory state (19,20).…”
Section: Introductionmentioning
confidence: 99%